Can a spreading flame over electric wire insulation in concurrent flow achieve steady propagation in microgravity? - Nagachi, Masashi; Mitsui, Fumiya; Citerne, Jean-Marie; Dutilleul, Hugo; Guibaud, Augustin; Jomaas, Grunde; Legros, Guillaume; Hashimoto, Nozomu; Fujita, Osamu (Proceedings of the Combustion Institute, 2019)
Concurrent flame spread over electric wire insulation was studied experimentally in microgravity conditions during parabolic flights. Polyethylene insulated Nickel-Chrome wires and Copper wires were examined for external flow velocities ranging from 50 mm/s to 200 mm/s. The experimental results showed that steady state flame spread over wire insulation in microgravity could be achieved, even for concurrent flow. A theoretical analysis on the balance of heat supply from the flame to the unburned region, radiation heat loss from the surface to the ambient and required energy to sustain the flame propagation was carried out to explain the presence of steady spread over insulated wire under concurrent flow. Based on the theory, the change in heat input (defined by the balance between heat supply from flame and radiation heat loss) was drawn as a function of the flame spread rate. The curve intersected the linear line of the required energy to sustain the flame. This balance point evidences the existence of steady propagation in concurrent flow. Moreover, the estimated steady spread rate (1.2 mm/s) was consistent with the experimental result by considering the ratio of the actual flame length to the theoretical to be 0.5. Further experimental results showed that the concurrent flame spread rate increased with the external flow velocity. In addition, the steady spread rate was found to be faster for Copper wires than for Nickel-Chrome wires. The experimental results for upward spreading (concurrent spreading) in normal gravity were compared with the microgravity results. In normal gravity, the flame did not reach a steady state within the investigated parameter range. This is due to the fact that the fairly large flame spread rate prevented the aforementioned heat balance to be reached, which meant that such a spread rate could not be attained within the length of the tested sample.